Hegel, Georg Wilhelm Friedrich (1770-1831) - Wildenauer, Miriam (International encyclopedia of the social & behavioral sciences, 2001)
G. W. F. Hegel (1770-1831) was one of the last great philosophers, who developed a system of all philosophical sciences: Logic, Philosophy of Nature, and Philosophy of Spirit. This article gives an outline about his life, his philosophy, and his influence on the social sciences. Hegel was born in Stuttgart (Germany), educated at the University at Tübingen, and worked as a private tutor in patrician families in Bern and Frankfurt. He began his academic career as an Associate Professor in Jena, was then editor of a daily newspaper of Bamberg, and then principal of a secondary school in Nuremberg for eight years. He then taught as a regular professor at the University of Heidelberg (1816) and at the University of Berlin (1818-1831). His main works are Phenomenology of Spirit (1807), Science of Logic (1812-1816), Encyclopedia of the Philosophical Sciences in Outline(1817, 1827, and 1831), and Elements on the Philosophy of Right (1821). In the development of the social sciences Hegel's philosophy not only influenced Karl Marx, but, what is less known, also influenced Lorenz von Stein, the St. Louis Hegelians, Wilhelm Wundt, G. H. Mead, and Juergen Habermas.